공기 포일 베어링으로 지지되는 초고속 마이크로 터보차져의 구동 안정성 향상에 관한 연구 - 곽용석; 정진택; 이용복; 김창호 (대한기계학회, 2008)
To improve the operational stability of the 100 Watts class Micro Gas Turbine, the air foil bearing with additional damping material has been investigated. The key of structure is that a viscoelastic material is coated under the top foil. The compliant foil journal bearing and thrust bearing are designed to withstand high load of vibrations at the operational speed 870,000 rpm. Test is executed in room temperature. Rotor has stably operated above 480,000 rpm. It is over 55% of the designed speed 870,000 rpm. Synchronous and subsynchronous vibrations are both well controlled. Vibration amplitude diminished over 50%. With the help of increased damping resulting from the viscoelasticity, the rotor stability of Micro turbocharger has been improved